2016
DOI: 10.1016/j.jamcollsurg.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resident Involvement in Surgery (IRIS-NSQIP): Looking at the Bigger Picture Based on the American College of Surgeons-NSQIP Database

Abstract: Our study confirms that, across different surgical subspecialties, resident involvement in surgery is associated with comparable morbidity and lower mortality outcomes. This provides a reassuring answer to patients, attending surgeons, and surgical program directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…As procedural volume for TKA continues to rise, attendings may be more inclined to allow trainees to assist in arthroplasty procedures. Previous studies have shown a high proportion of resident involvement in cases in NSQIP [10,28], and therefore, a rise in operative time across the included years may be expected. However, this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…As procedural volume for TKA continues to rise, attendings may be more inclined to allow trainees to assist in arthroplasty procedures. Previous studies have shown a high proportion of resident involvement in cases in NSQIP [10,28], and therefore, a rise in operative time across the included years may be expected. However, this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, our policy is that every surgical procedure has to be at least assisted by a board-certified surgeon and that steps of every operation have to be assisted whenever possible. Data from various analysis of the American NSQIP database show that outcomes are not influenced by resident involvement [ 24 ]. Moreover, every patient requires presentation in a multidisciplinary tumor board.…”
Section: Discussionmentioning
confidence: 99%
“…17 This potential risk is balanced by studies suggesting that, in general, patients do not have worse outcomes if residents are involved in their surgical procedure. 18 The unique responsibilities and contributions of teaching hospitals should be recognized by funding bodies and activitybased funding should account for the increased operative time associated with training the next generation of medical professionals.…”
Section: Discussionmentioning
confidence: 99%